Half-life of exogenous growth hormone following suppression of endogenous growth hormone secretion with somatostatin in type I (insulin-dependent) diabetes mellitus. - Mullis, P; Pal, B; Matthews, DR; Hindmarsh, P; Phillips, P; Dunger, D (1992)
OBJECTIVE: To estimate the half-life of growth hormone in young adult patients with type I (insulin-dependent) diabetes mellitus following bolus injection and prolonged exposure for the purpose of deconvolution analysis of plasma growth hormone profiles to determine growth hormone secretory rates. DESIGN: In the bolus study, an intravenous bolus injection of 100 mU of biosynthetic human growth hormone was given while endogenous growth hormone was suppressed by a continuous infusion of somatostatin under three different glucose clamp conditions: normoglycaemia (5 mmol/l) with normoinsulinaemia (65 pmol/l); hyperglycaemia (12 mmol/l) with normoinsulinaemia; and normoglycaemia with hyperinsulinaemia (360 pmol/l). In the infusion study, the effect of prolonged and repeated growth hormone exposure upon the growth hormone half-life was estimated. Three pulses of 60 minutes growth hormone infusion (6 mU/kg/pulse) two hours apart under euglycaemic somatostatin suppression were applied. PATIENTS: Six young adult patients with type I (insulin-dependent) diabetes mellitus were studied in both the bolus and the infusion study. RESULTS: Mean GH half-lives by mono-exponential analysis were not significantly different remaining unaltered by the short-term metabolic changes of hyperglycaemia and hyperinsulinaemia. Data were therefore pooled yielding an overall mean GH half-life of 13.6 minutes (range 11.9-19.4). Applying a bi-exponential model mean GH half-lives were 3.1 minutes (range 2.5-5.9) for the rapid phase of distribution of the hormone and 13.8 minutes (range 9.6-16.9) for the decay of GH from the circulation. The GH half-life during the infusions studies did not vary with repeated exposure but was significantly longer (mean half-life of 25.7 minutes; range 19.4-37.1) than during the bolus studies (P less than 0.001). CONCLUSIONS: The half-life of exogenous r-hGH is not affected by glucose or insulin concentrations but increases after prolonged GH exposure in young adults with type I (insulin-dependent) diabetes mellitus.